Translational Dynamics in Urban Space: Exploring Battala’s Multilingual Cultural Encounter - Das, Pratim; Pareek, Sushmita (Text Matters: A Journal of Literature, Theory and Culture, 2025)
“Battala” is a Bengali metonym for commercial print culture which gained popularity during the Bengal Renaissance. This print culture became a translational palimpsest, disseminating literary genres and leading to the creation of a site where high and low culture converged. Our paper examines the complex relationship between 19th-century colonial Calcutta and the languages in this fast-developing city. The popular print culture blurred distinctions between cultural forms, transcending geographical and literary boundaries of the colonial cosmopolis. This paper contributes to the discourse on translating otherness in the city by demonstrating how Battala intricately reflected relationships between language, memory, and urban space within the historical and cultural context of colonial Calcutta. This is done through an analysis of selected works, including Koutuk Shatak by Harishchandra Mitra, Rar Bhar Mithya Katha Tin Loye Kolikata by Pyarimohan Sen, and Ki Mojar Koler Gari by Munsi Azimuddin. Other works that highlight the blurring of cultural spaces include the translation of The Arabian Nights by Avinash Chandra Mitra (titled Sachitra Ekadhik Sahasra Dibas). Additionally, translations of Ameer Hamzar Puthi by Abdun Nabi and Shah Muhammad Saghir’s Yūsuf Zuleikhā show significant Urdu and Arabic-Persian influence. By analyzing Battala’s interactions with marketplaces, different communities, and intellectual salons, this study adds to the interdisciplinary discussion on translation and urban space. It examines the city’s symbolic representations in popular literature, as well as its geographic location and social significance.